The metabolic profiles and body composition of non-obese metabolic associated fatty liver disease - Zhang, Yujuan; Xiang, Liulan; Qi, Fang; Cao, Yutian; Zhang, Wenhui; Lv, Tiansu; Zhou, Xiqiao (Frontiers in Endocrinology, 2024)
Background/purpose Metabolic-associated fatty liver disease (MAFLD) is a major cause of chronic liver disease worldwide and is generally thought to be closely related to obesity and diabetes. However, it also affects non-obese individuals, particularly in Asian cultures.Methods Healthy physical examination subjects and MAFLD patients were included in the endocrinology department of Jiangsu Provincial Hospital of Traditional Chinese Medicine. MAFLD was defined as fatty liver in imaging without virus infection, drug, alcohol, or other known causes of chronic liver disease. Non-obese MAFLD was defined as MAFLD in non-obese subjects (BMI<25 kg/m2).The final analysis comprised 1047 participants in total. Of 946 MAFLD patients, 162 (17.12%) were diagnosed with non-obese MAFLD. Non-obese MAFLD patients were older, had lower alanine aminotransferase (ALT), triglyceride, and waist circumference, but had higher high density lipoprotein cholesterol (HDL-c) than obese MAFLD patients. Compared with non-obese healthy controls, non-obese MAFLD patients had higher BMI, ALT, gamma-glutamyl transferase (GGT), uric acid (UA), triglycerides (TG), and low density lipoprotein cholesterol (LDL-c). In terms of body composition, body fat mass (BFM), waist-hip ratio (WHR), percent body fat (PBF), visceral fat area (VFA), and fat mass index (FMI) were lower in non-obese healthy controls than non-obese MAFLD patients. A binary logistic regression analysis revealed that non-obese MAFLD was linked with lower GGT and higher HDL-c.In this study cohort, non-obese MAFLD was present at a prevalence of 13.90%. In contrast to non-obese healthy controls, non-obese MAFLD patients exhibited different metabolic profiles, but they also had different body compositions.